GE_GERICHTE PS/74/2018 vom 22. November 2018 - GE Cour de justice (2018)
EXPULSION(DROIT PÉNAL) ; REPORT(DÉPLACEMENT) ; COMPÉTENCE FONCTIONNELLE ; COMPÉTENCE RATIONE MATERIAE | CP.66.letd; LaCP.40; LaCP.42; LaCP.5